2017
DOI: 10.1039/c6sm02431a
|View full text |Cite
|
Sign up to set email alerts
|

Thermal annealing behaviour and gel to crystal transition of a low molecular weight hydrogelator

Abstract: The thermal annealing behaviour of an electrolyte-triggered calixarene hydrogelator is found to depend strongly on the specific metal chloride used. While the lithium chloride gel showed typical gel-sol transitions as a function of temperature, the magnesium chloride gel was found to repeatedly strengthen with heat-cool cycles. Structural investigations using small-angle neutron scattering, and scanning probe microscopy, suggest that the annealing behaviour is associated with a change in morphology of the fibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 46 publications
2
16
0
Order By: Relevance
“…Indeed, although it has been widely assumed that there is a link, there are a number of examples that now specifically show that packing is different in the gel phase and crystals grown even from the same solvent. [24][25][26] As a specific example, we showed that fiber X-ray diffraction data from the gel phase did not match the crystal structure of a crystal grown directly from the gel phase. 24 In many cases, the crystals formed in one solvent are compared with a gel formed in another.…”
mentioning
confidence: 99%
“…Indeed, although it has been widely assumed that there is a link, there are a number of examples that now specifically show that packing is different in the gel phase and crystals grown even from the same solvent. [24][25][26] As a specific example, we showed that fiber X-ray diffraction data from the gel phase did not match the crystal structure of a crystal grown directly from the gel phase. 24 In many cases, the crystals formed in one solvent are compared with a gel formed in another.…”
mentioning
confidence: 99%
“…Recent studies gave much evidence to explore the properties of gel to crystal transition for peptide, amino acid and sugar derivatives. [42][43][44][45] However, there is no literature to report the detail crystallization process of guanosine-based hydrogels. To nd out and understand the reason for the crystallization of F G d hydrogel, the visualize dynamic crystal process of F G d hydrogel has been investigated as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[3] Since as table phase emerges at the expense of am etastable phase,g el-crystal transitions have been described to follow Ostwaldsr ule of stages, [4] as shown for other supramolecular systems. [7] Gel-crystal transitions have been reported for aw ide variety of supramolecular gelators,i ncluding sugars, [7,8] functionalized acids, [9] macrocycles, [10] and other molecules. [6] Notably,t he destabilizing gel-crystal transition is presently unavoidable by rational gelator design and has therefore invoked preventive formulation strategies.…”
Section: Introductionmentioning
confidence: 99%